Superconductors: Alkali‐Metal‐Intercalated Percolation Network Regulates Self‐Assembled Electronic Aromatic Molecules (Adv. Mater. 11/2019). Issue 11 (12th March 2019) - Hu, Yong; Zhong, Guohua; Guan, Ying‐Shi; Lee, Nam Hoon; Zhang, Yuan; Li, Yang; Mitchell, Travis; Armstrong, Jason N.; Benedict, Jason; Hla, Saw‐Wai; Ren, Shenqiang
Abstract : In article number1807178, Shenqiang Ren and co‐workers find evidence that potassium‐intercalation‐induced 1D dipole pairs in alkali‐metal‐intercalated p‐terphenyl molecular electronic crystals regulate both the conductivity and electronic and optical transitions. The light‐induced electron interactions enhance the charge‐carrier itinerancy, leading to a switchable metal‐to‐insulator transition, opening a route for the regulation of superconducting phase development and long‐term modulation of electronic efficacy in nanotechnologically important thin films.